PENERAPAN QUICK ON THE DRAW DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI SISWA KELAS XII IPS 2 SMA NEGERI 2 PEKANBARU - Tini, Ratna (UIR Press, 2016)
This research is a classroom action research that aims to improve the learningprocess and improve learning outcomes of economics students with the application ofQuick On The Draw in cooperative learning. The subjects were students of class XIIIPS 2 SMA Negeri 2 Pekanbaru in the first semester of the academic year 2013/2014,totaling 40 people, consisting of 19 male students and 21 female students withacademic ability levels are heterogeneous. The study consisted of two cycles, each cycleconsisting of four phases: planning, implementation, observation and reflection. Eachend of the cycle carried out daily tests. The data collection is done by observationtechniques and techniques written test. Data was analyzed using descriptive qualitativeanalysis techniques of narrative and descriptive statistical analysis. Results of researchon the observation sheet shows the activity of teachers and students have done wellafter taking action even though there are still some deficiencies. Teacher activity inaccordance with the planning and activities of students also increased to be active bothin discussions and when answering a question card set. Criteria for success of theaction on this study is the result of increased student learning that can be seen from theincreasing value of students can be seen from the analysis of the achievement of KKM.If the number of students who reach KKM on daily tests 1 and 2 daily test more than thebasic score, it can be said Shiva value increases. The number of students who reachKKM on a base score, daily test I (first cycle), daily test II (second cycle) respectivelyare 30%, 50% and 75%. The results of this study indicate that the application of QuickOn The Draw in cooperative learning can improve student learning outcomes economyclass XII IPS 2 SMA Negeri 2 Pekanbaru semester of academic year 2013/2014.